Latex allergy: assessment of knowledge, appropriate use of gloves and prevention practice among hospital healthcare workers. (1st October 2012) - Al‐Niaimi, F.; Chiang, Y. Z.; Chiang, Y. N.; Williams, J.
Summary Background. Healthcare workers and patients are often exposed to natural rubber latex (NRL) through contact with gloves and various healthcare products, which can potentially cause allergic reactions, with varying degrees of severity. In 2008, the Royal College of Physicians published their first evidence‐based guidance on occupational health interventions for latex allergy, which emphasized the importance of healthcare workers having knowledge of latex allergy. Aim. This study aimed to survey the knowledge of healthcare workers (n = 156) about latex gloves and NRL allergy, routine prevention practice and the appropriate use of gloves in patient care. Methods. Healthcare workers in a large teaching hospital were surveyed using a standard questionnaire. Results. We found that only 1% of healthcare workers were able to correctly match the appropriate gloves to the specifically designed procedure. More than half (n = 74.53%) were unable to recognize the presentation of type 1 allergy to NRL. Of the 156 participants, 131 (84%) considered that they would benefit from training about NRL allergy and the use of different types of gloves in clinical care. Conclusions. This survey indicates the importance of education regarding appropriate use of gloves and prevention of NRL allergy among healthcare workers, and dermatologists should play an important role in facilitating this.